2018
DOI: 10.1007/s12098-018-2676-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Presepsin Obtained from Tracheal Aspirates in the Diagnosis of Early Onset Pneumonia in Intubated Newborns

Abstract: In intubated newborns, measurements of presepsin obtained from tracheal aspirate suggested that it can be used as a complementary marker in diagnosing early onset neonatal pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…PSP have been recently described to be increased in APTB patients, thus it could be helpful in the initial differential diagnosis between APTB and BCAP. Pneumonia development is also a challenging aspect of the intubated newborn [18], where blood sample collection is critical. In this context, PSP measurement in the tracheal aspirate was recently suggested as a complementary marker in the diagnosis of early onset neonatal pneumonia [19].…”
Section: Psp In Pulmonary Infectionsmentioning
confidence: 99%
“…PSP have been recently described to be increased in APTB patients, thus it could be helpful in the initial differential diagnosis between APTB and BCAP. Pneumonia development is also a challenging aspect of the intubated newborn [18], where blood sample collection is critical. In this context, PSP measurement in the tracheal aspirate was recently suggested as a complementary marker in the diagnosis of early onset neonatal pneumonia [19].…”
Section: Psp In Pulmonary Infectionsmentioning
confidence: 99%
“…Presepsin, soluble CD14 subtype (sDC14-ST), is well known biomarker of systemic bacterial infections. Isolated from blood, it proved to be more accurate biomarker of earlyonset sepsis compared to procalcitonin (PCT) and C-reactive protein (CRP) (8,9). Obtained from tracheal aspiration presepsin proved to be significant in the diagnosis of early neonatal pneumonia (9).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated from blood, it proved to be more accurate biomarker of earlyonset sepsis compared to procalcitonin (PCT) and C-reactive protein (CRP) (8,9). Obtained from tracheal aspiration presepsin proved to be significant in the diagnosis of early neonatal pneumonia (9). Variables that are affecting C-reactive protein and procalcitonin values do not affect presepsin levels.…”
Section: Introductionmentioning
confidence: 99%
“…A recent metaanalysis reported that serum presepsin had greater sensitivity than C-reactive protein and procalcitonin for detection of sepsis [5]. In this issue of the journal, Savić et al [6] studied 60 neonates ≥24 wk of gestation who were intubated and mechanically ventilated on the first day of life. These neonates were then classified into those with suspected pneumonia (n = 36) and others without pneumonia (n = 26), who were also control group.…”
mentioning
confidence: 99%
“…In the publication by Savić et al [6], the working definition of pneumonia was any two positive out of three criteria, clinical, radiological and microbiological, that is blood culture. However the distribution of these among cases and controls has not been given.…”
mentioning
confidence: 99%